Thank You to Our 2022 Peer Reviewers - Stephen M. Griffies; Jiwen Fan; Natasha MacBean; Tapio Schneider (Journal of Advances in Modeling Earth Systems, 2023)
Abstract The editors of Journal of Advances in Modeling Earth Systems thank the 702 reviewers who provided 1362 reviews during 2022. Their hard work and insights, typically done anonymously, benefits authors, readers, and the broader science community.